A chemical deposition process for low-cost CZTS solar cell on flexible substrates. (21st March 2017) - Boshta, Mostafa; Binetti, Simona; Le Donne, Alessia; Gomaa, Mohamed; Acciarri, Maurizio
Abstract : Cu2 ZnSnS4 (CZTS) thin films and solar cells were successfully prepared using a new process based on spray pyrolysis technique. The main advantage of the proposed process is the avoiding of sulphurisation process at high temperature and in toxic gases like H2 S. X-ray diffraction studies and Raman spectroscopy confirmed the formation of good-quality microcrystalline CZTS films in a tetragonal structure. Optical measurements showed that CZTS films have a direct band gap and high absorption coefficient (4 × 10 4 cm −1 ) as requested for solar cell application. CZTS solar cell prototypes deposited on low-cost flexible plastic substrates were prepared and tested.